Great Southern Lands: Making Space for Teacher Resilience in South Africa and Australia - Mansfield, C.; Ebersöhn, L.; Beltman, Susan; Loots, T. (Springer, 2018)
Teacher resilience is an issue of international concern yet few cross-national studies exist. This chapter examines teacher resilience in two postcolonial, economically disparate, Southern hemisphere contexts: South Africa and Australia. Data from studies in each country are examined to investigate the nature of risks and resources to support teacher resilience in each context. A conceptual model is developed to illustrate how the ecologies in these two countries differ with regards to the specific adversities teachers face, as well as protective resources available to teachers to buffer against such risk. Findings show that irrespective of context, certain teacher personal resources (optimism, perseverance, motivation) and adaptive coping strategies (relational support, problem-solving) remain similar across dissimilar contexts. In addition, while the broad origin of the risks was similar, how these were manifested differed in each context due to broader socio-economic conditions. Implications for further research, teacher preparation and professional development are discussed